Google Maps API as a Tool for Detecting Urban Density Levels - Ara Kian, Donatus; Sanjaya, Ridwan; Rejeki, V. G. Sri (CV. Gio Architect, 2026)
The development of geospatial technology has enabled more efficient analyses of urban density. Google Maps API provides location data, traffic information, and user activity patterns that can be utilized to detect density levels in urban areas. This study aims to explore the potential of the Google Maps API as a tool for identifying urban density by integrating traffic data (Traffic Layer), business location datasets, and user movement patterns. The findings indicate that data obtained from the Google Maps API can be used to map high-density zones in both real-time and historical contexts. These insights have significant implications for urban planning, congestion mitigation, and smart city development.